The mediating role of presence differs across types of spatial learning in immersive technologies. (June 2020) - Parong, Jocelyn; Pollard, Kimberly A.; Files, Benjamin T.; Oiknine, Ashley H.; Sinatra, Anne M.; Moss, Jason D.; Passaro, Antony; Khooshabeh, Peter
Abstract: The effects of immersive technology on learning have been mixed. It is therefore important to determine the factors that affect when and why immersive technologies are and are not effective. One psychological construct proposed to explain why higher levels of immersive technology may lead to better learning compared to lower immersion is presence, or the subjective feeling of "being there." Participants completed a spatial task in three levels of immersive technology, reported the amount of presence felt, and completed learning outcome tasks measuring three levels of spatial knowledge: landmark, route, and survey knowledge. The relationships between the level of immersive technology, presence, and spatial learning outcomes were examined. The highest immersion condition led to better performance on landmark, route, survey, and overall spatial knowledge, and also led to higher levels of presence. Higher presence led to better performance on route, survey, and overall spatial knowledge. However, presence only significantly mediated the relationship for survey knowledge, and effects of low vs. medium immersion condition on learning and presence often did not differ, despite the devices having largely different affordances. The relationship between immersion and learning is thus complex, depends on type of learning, and may be mediated by both presence and non-presence effects on cognitive load. Highlights: Technologies with high immersion led to better spatial learning than those with low immersion. High immersion also led to higher levels of reported presence than low immersion. Higher presence was associated with better performance on spatial learning outcomes. The learner's presence mediated the relationship only for survey knowledge questions. Presence effects varied by task level, which may reflect different types of cognitive load.